Generation of ultrashort laser pulses : Use of heavily doped germanosilicate fibres with a small core diameter in stretchers of ultrashort laser pulses at a wavelength of 1.03 μm. (20th August 2019) - Khudyakov, D V; Ganin, D V; Lyashedko, A D; Borodkin, A A; Likhachev, M E; Salganskii, M Yu; Vartapetov, S K
Abstract: The use of a heavily doped germanosilicate fibre with a W-profile refractive index and small core diameter in stretchers of ultrashort laser pulses with their subsequent amplification and compression in all-fibre laser systems is considered. The application of fibres of this type makes it possible to stretch, amplify, and then compress a laser pulse with minimum distortions of its initial shape and width. Due to the dispersion properties of these fibres, which allow the pulse duration to be increased significantly at a small fibre length and the third-order positive dispersion of the diffraction-grating-based output compressor to be compensated for, amplified pulses with an energy of 2 μJ and width of 250 fs, free of a picosecond pedestal, are obtained. Several types of fibres intended for the use in stretchers of ultrashort laser pulses are comparatively analysed from the point of view of their dispersion compatibility with a diffraction-grating-based output compressor.